A Multi-Criteria Analysis GIS Tool for Measuring the Vulnerability of the Residential Stock Based on Multidimensional Indices - Itziar Modrego-Monforte; Mikel Barrena-Herrán; Olatz Grijalba (Land, 2023)
There is extensive scientific evidence showing that the characteristics of the urban and residential environment directly affect people’s quality of life and health. In this framework, numerous building renovation policies have been developed in Europe, mainly focused on improving energy efficiency. However, we are dealing with a multifactorial and multicausal phenomenon of a complex system where competent institutions need quantitative diagnosis mechanisms that consider this holistic vision when making decisions and prioritizing interventions. Regarding this, the present research develops the potential of the multi-criteria methodology in a first proposal, which integrates social, energy, environmental and spatial aspects linked to the relationship between housing and the effects on the health of its inhabitants. It is a multidimensional method based on systematized and exportable vulnerability indices, which applies indicators that have been calculated using cadastral data and a typomorphological characterization of the residential stock. The analysis of the results through geostatistical techniques of autocorrelation and clustering applied to the case study of Donostia-San Sebastián shows that the proposed methodology is effective in achieving the objectives set. The associated GIS tool has proved to be agile and replicable.